RUMPI 'LITERACY THROUGH ACTION' FOR EMPOWERING TANI MANDIRI SMALLHOLDERS TOWARD SUSTAINABLE OIL PALM INNOVATION - Delyana Rahmawany Pulungan; Mhd. Andi Rasyid; Dina Arfianti Saragih; Tifany Zia Aznur; Ritna Wahyuni; Delyanti Azzumarito Pulungan (RADJA PUBLIKA, 2026)
Smallholder oil palm plantations occupy a strategic position in Indonesia's palm oil supply chain, yet their sustainability remains constrained by gaps in Good Agricultural Practices (GAP), land legality and farm records, occupational safety, and environmental protection. This community service program aimed to improve green literacy on RSPO-based GAP through the RUMPI Innovation (Rumah Pintar Petani/Farmers' Smart House) at the Tani Mandiri Farmer Group Association, Laut Tador Village, Batu Bara Regency. The program used an integrative, participatory, and replicable approach combining needs assessment, socialization, experiential learning, group discussion, field demonstration, and mentoring. The main educational activity was conducted on 21 June 2026 with 50 farmers. Pre-test and post-test questionnaires assessed sustainable plantation knowledge, RSPO literacy and readiness, farm practices, and participant responses. The total green literacy index increased from 44.4 to 63.2, indicating moderate improvement. The strongest gains occurred in knowledge and readiness, while consistent on-farm implementation still required continued mentoring. RUMPI extended extension services from information transfer to 'literacy through action' by linking standards, field practices, digital information, and institutional strengthening. The program supports continuous improvement and the group's long-term readiness to maintain RSPO certification